Konflikt interesu publicznego z prywatnym na tle instytucji wywłaszczenia nieruchomości - Stawecki, Marek (Annales. Etyka w Życiu Gospodarczym, 2012)
Ownership, as a basic value of a legal state is the subject to special protection guaranteed by a basic law. However, in certain situations acting for the benefit of public interest is, according to a legislator, takes priority over private ownership. Thus, in cases when public interest is at stake limitation of ownership title to property can be permitted by regulations. Expropriation of private property for the sake of public good is the solution used for many years in Poland and in other countries. Basic preconditions for expropriation are described in art. 21 section 2 of The Constitution of the Republic of Poland. Private ownership in art. 21 of Polish Constitution was defined in a very general context without defining the subject. Thus, all the ownership is the subject to state protection without specifying the principles of this protection, which are regulated by ordinary acts. Guaranteeing right to private ownership does not mean the right is inviolable. Constitution allows for property expropriation for the benefit of public purposes after a just compensation. However, it must be emphasized that regulations relating to the rules of property expropriation as a special form of depriving ownership right by means of authoritarian state act, which is the exception from general civil and legal principles of transferring ownership title, must be applied literally, excluding admissibility of extensive interpretation. Provisions of the constitution are defined in the regulations of the Real Estate Management Act from 21st August 1997.